Pola Religiositas Muslim Kelas Menengah di Perkotaan - Rofhani Rofhani (Department of Religious Studies, Faculty of Ushuluddin and Philosophy, Sunan Ampel State Islamic University Surabaya, 2013)
A city, modern in culture, offers variety of happiness, pleasures that similar with the paradise in the world as mentioned in the holy scriptures. People think that such condition commonly lead to a negative assumption referring to people religious moral ethic. In one occasion, such condition effect to the fundamental movement that offers Islamic culture. However, it does not work on a certain group of people. In one hand, those who are called as urban middle class Muslim mostly refuse any fundamental culture that have believed as ways, ancient, traditional or even a backward. On the other hand, they also reject western culture since some assess that it can harm Islamic religion internally and externally. In this regard, this article aims to describe religious patterns of middle class society which is living in the city, where chronicles of modernity have appeared with their very artificial forms. For some people, living in the city is assumed as a threatening life to weaken morality. This creates such as fundamental movements with their imaginative Islamic objectives. They offer to acknowledge a modern and Islamic style of live. Exploring academic discourse of modernity, religion, and culture, this article elucidates the modern Islamic pattern of life within middle class Muslim in the city.